Transcriptome Analysis and Characterization of Chemosensory Genes in the Forest Pest, Dioryctria abietella (Lepidoptera: Pyralidae) - Wang, Zheng-Quan; Wu, Chun; Li, Gen-Ceng; Nuo, Shu-Mei; Yin, Ning-Na; Liu, Nai-Yong (Frontiers in Ecology and Evolution, 2021)
In Lepidoptera, RNA sequencing has become a useful tool in identifying chemosensory genes from antennal transcriptomes, but little attention is paid to non-antennal tissues. Though the antennae are primarily responsible for olfaction, studies have found that a certain number of chemosensory genes are exclusively or highly expressed in the non-antennal tissues, such as proboscises, legs and abdomens. In this study, we report a global transcriptome of 16 tissues from Dioryctria abietella, including chemosensory and non-chemosensory tissues. Through Illumina sequencing, totally 952,658,466 clean reads were generated, summing to 142.90 gigabases of data. Based on the transcriptome, 235 chemosensory-related genes were identified, comprising 42 odorant binding proteins (OBPs), 23 chemosensory proteins (CSPs), 75 odorant receptors (ORs), 62 gustatory receptors (GRs), 30 ionotropic receptors (IRs) and three sensory neuron membrane proteins (SNMPs). Compared to a previous study in this species, 140 novel genes were found. A transcriptome-wide analysis combined with PCR results revealed that except for GRs, the majority of other five chemosensory gene families in Lepidoptera were expressed in the antennae, including 160 chemosensory genes in D. abietella. Using phylogenetic and expression profiling analyses, members of the six chemosensory gene repertoires were characterized, in which 11 DabiORs were candidates for detecting female sex pheromones in D. abietella, and DabiOR23 may be involved in the sensing of plant-derived phenylacetaldehyde. Intriguingly, more than half of the genes were detected in the proboscises, and one fourth of the genes were found to have the expression in the legs. Our study not only greatly extends and improves the description of chemosensory genes in D. abietella, but also identifies potential molecular targets involved in olfaction, gustation and non-chemosensory functions for control of this pest.